2022
DOI: 10.3389/fmed.2022.1000563
|View full text |Cite
|
Sign up to set email alerts
|

Cholecystectomy promotes the development of colorectal cancer by the alternation of bile acid metabolism and the gut microbiota

Abstract: The incidence and mortality of colorectal cancer (CRC) have been markedly increasing worldwide, causing a tremendous burden to the healthcare system. Therefore, it is crucial to investigate the risk factors and pathogenesis of CRC. Cholecystectomy is a gold standard procedure for treating symptomatic cholelithiasis and gallstone diseases. The rhythm of bile acids entering the intestine is altered after cholecystectomy, which leads to metabolic disorders. Nonetheless, emerging evidence suggests that cholecystec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 160 publications
0
8
0
Order By: Relevance
“…Cholecystectomy is a common surgical procedure. At present, many studies have found that the incidence of colon cancer increases with the extension of cholecystectomy time [9,21], which is associated with altered gut microbiota and disturbed bile acid metabolism [12]. However, most of studies focused on the detection of stool samples.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cholecystectomy is a common surgical procedure. At present, many studies have found that the incidence of colon cancer increases with the extension of cholecystectomy time [9,21], which is associated with altered gut microbiota and disturbed bile acid metabolism [12]. However, most of studies focused on the detection of stool samples.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, the exposure of the bile acid pool to intestinal bacteria increases, leading to an increase in the proportion of secondary bile acids(especially deoxycholic acid and lithocholic acid) in patients' feces [11]. Notably, these secondary bile acids have been con rmed to be carcinogenic on CRC [12]. In addition, several studies focused on gut microbiota in PC patients and found that cholecystectomy can signi cantly change the ecological status of intestinal bacteria [9,[13][14][15], which may involve in diarrhea [14], CRC [9] and metabolic related diseases [16][17][18][19] after the operation.…”
Section: Introductionmentioning
confidence: 99%
“…However, other studies have found no difference in the composition of bile before and after cholecystectomy [19][20][21]. A recent review has reported that the altered metabolism of BAs and the change in the composition of the intestinal microbiome play a role in the development of CRC [22]. However, the exact mechanism is still completely unclear.…”
Section: Introductionmentioning
confidence: 99%
“…This standard of care in treating gallbladder disease by cholecystectomy results in removal of the storage container of bile, and therefore bile is directly released into the small intestine during digestion without the typical rate and flow control of the gallbladder. 4 Previous studies are inconclusive as to whether the removal of the gallbladder results in increased, decreased, or unchanged circulation of bile acids. However, one study of mice postcholecystectomy revealed an increased bacterial 1 Atrium Health Wake Forest Baptist Medical Center, Winston-Salem, NC, USA 2 Duke University Health System in Durhum, NC, USA production of secondary bile acids, such as LCA and DCA.…”
mentioning
confidence: 99%
“…However, one study of mice postcholecystectomy revealed an increased bacterial 1 Atrium Health Wake Forest Baptist Medical Center, Winston-Salem, NC, USA 2 Duke University Health System in Durhum, NC, USA production of secondary bile acids, such as LCA and DCA. 4 The exact role that cholecystectomy plays in alteration of bile acids and therefore its indirect effect on breast cancer development, progression, and recurrence is an important risk factor to explore. As breast cancer is the most common cancer in women worldwide, understanding the impact of cholecystectomy on bile acids and breast cancer could create a new treatment target or identifiable risk factor.…”
mentioning
confidence: 99%